Criminal liability for injuries of competitors arising in the course of sports competition in Polish criminal law - TOMASZ WALDZIŃSKI; CEZARY WALDZIŃSKI; ALEKSANDRA DURZYNSKA; EWA WALDZIŃSKA; MAŁGORZATA KNAŚ; KAZIMIERZ KOCHANOWICZ (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Practicing both high performance and recreational sport involves not only many sacrifices, taking care of one's health and maintaining an appropriate shape, but also risks which result in damage to one's health and, in extreme cases - the death of a contestant. The athletes suffer various types of sports injuries during competitions or training sessions. Much of it is due to the behaviour of another contestant. Therefore, the question is when a sportsman, in the Polish legal system, will be liable for a penalty for the fact that during the competition he caused an injury (sporting injury) to his rival. The criminal liability of sportsmen may be subject to criminal law provisions concerning: causing serious bodily harm, causing other than serious bodily harm, unintentionally causing the death, violating personal inviolability. According to the criminal law, an injury caused as a result of sports activity should be defined as a bodily harm. It should also be pointed out that in the Polish legal system it has been developed by doctrine and reflected in court rulings, the sport risk justification excluding the unlawfulness of the act and thus excluding criminal liability of the competitor causing damage to the health or death of the competitor.